KLF15-POU3F4 axis activates PI3K/AKT signaling to promote glioma progression - Wang, Dong; Yu, Wan; Wang, Ran; Liu, Ning (Translational Cancer Research, 2026)
Background: Glioma is a highly aggressive brain tumor with poor prognosis, necessitating new biomarkers and therapeutic targets. This study aimed to explore the role of Pit-Oct-Unc class 3 homeobox 4 (POU3F4) in glioma using bioinformatics analysis and experimental verification.Methods: Bioinformatics analysis was performed using the public databases The Cancer Genome Atlas (TCGA) and The Cancer Imaging Archive Atlas (ATLAS) to explore POU3F4 expression and prognosis in gliomas. Samples were collected from clinical glioma tissues, paracancerous tissues, and plasma of patients and healthy candidates. POU3F4 expression was examined using molecular biological methods, and its potential diagnostic value was assessed. In vitro, normal human astrocytes (NHAs) and various glioma cells (U87MG, U251MG, T98G, A172, and LN229) were used to assess POU3F4 expression using quantitative polymerase chain reaction (qPCR) and western blotting (WB). U87MG and U251MG cells were transfected with specific small interfering RNAs (siRNAs) of POU3F4. The effects of POU3F4 siRNA on cell proliferation, apoptosis, and migration were assessed using the Cell Counting Kit-8 (CCK-8), clone formation, 5-ethynyl-2’-deoxyuridine (EdU), terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL), wound healing, and Transwell assays. The binding of KLF15 to the promoter region of POU3F4 was validated using chromatin immunoprecipitation (ChIP) assay. Finally, the molecular mechanism of KLF15-POU3F4 axis in regulating the PI3K/AKT signaling pathway was preliminarily explored by measuring the phosphorylation levels of phosphatidylinositol 3-kinase (PI3K) and protein kinase B (AKT).Results: Bioinformatics analysis revealed that POU3F4 levels were increased in gliomas, and upregulated POU3F4 may be associated with poor prognosis. Additionally, clinical sample analysis confirmed that POU3F4 was overexpressed in glioma tissues and plasma samples, and its levels in glioma tissues were positively associated with those in the plasma. The receiver operating characteristic (ROC) curve demonstrated that POU3F4 levels in both tissue and plasma exhibited good diagnostic value for glioma. In vitro experiments demonstrated that POU3F4 was overexpressed in different gliomas. POU3F4 knockdown reduced the growth and metastasis of glioma cells and increased apoptosis. Mechanistic studies demonstrated that POU3F4 knockdown did not affect the messenger ribonucleic acid (mRNA) or protein expression of PI3K or AKT but significantly reduced their phosphorylation. In addition, JASPAR database prediction and ChIP experiments confirmed that KLF15 is an upstream transcription factor of POU3F4, which can directly bind to the POU3F4 promoter region and positively regulate its expression. Functional recovery experiments have shown that the KLF15-POU3F4 axis promotes the proliferation, migration, and invasion of glioma cells by activating the PI3K/AKT signaling pathway.Conclusions: POU3F4 was upregulated in glioma and facilitated glioma cell growth and metastasis while suppressing apoptosis. KLF15 is its upstream transcription factor that positively regulates the expression of POU3F4. The KLF15-POU3F4 axis promotes glioma progression by activating the PI3K/AKT signaling pathway.